Introduction of Herbarium and Identification of Plants Based on School Environments in MTs. Negeri 2 Gorontalo Regency - D. Mamu, Hartono; Mardin, Herinda; Bunga Pagalla, Devi; Mustaqimah, Nur; Fajryani Usman, Nurul (ISAS (Indonesian Society of Applied Science), 2022)
The introduction of herbariums in schools as a medium to concrete material and support science learning and plant identification based on a school environment that makes it easier to teach material on the structure and function of plants in class VIII at Madrasah Tsanawiyah Negeri 2 Gorontalo district is the goal in this service activity. The stages of activities using an active participatory approach consist of 4 stages, namely 1) preparation; 2) coordination; 3) implementation; 4) evaluation. The number of students who took part in the activity was 30 people and was attended by the principal and 3 teachers. The herbarium introduction and plant identification activities based on the school environment went smoothly and wisely, as seen from the enthusiasm of the participants in participating in the activity from start to finish. The introduction of the herbarium gives meaning and impression to MTs students. Negeri 2 Gorontalo district because it is able to provide knowledge to students about one method/media to determine plant taxon. Identification of plants based on the school environment provides knowledge and skills to MTs students. Negeri 2 Gorontalo district in supporting learning activities in schools regarding the introduction and description of plants.